Delphinidin enhances radio-therapeutic effects via autophagy induction and JNK/MAPK pathway activation in non-small cell lung cancer - Kang, Seong Hee (Korean J Physiol Pharmacol, 2020)
Delphinidin is a major anthocyanidin compound found in various vegetables and fruits. It has anti-oxidant, anti-inflammatory, and various other biological activities. In this study we demonstrated the anti-cancer activity of delphinidin, which was related to autophagy, in radiation-exposed non-small cell lung cancer (NSCLC). Radiosensitising effects were assessed in vitro by treating cells with a sub-cytotoxic dose of delphinidin (5 µM) before exposure to γ-ionising radiation (IR). We found that treatment with delphinidin or IR induced NSCLC cell death in vitro; however the combination of delphinidin pre-treatment and IR was more effective than either agent alone, yielding a radiation enhancement ratio of 1.54 at the 50% lethal dose. Moreover, combined treatment with delphinidin and IR, enhanced apoptotic cell death, suppressed the mTOR pathway, and activated the JNK/MAPK pathway. Delphinidin inhibited the phosphorylation of PI3K, AKT, and mTOR, and increased the expression of autophagy-induced cell death associated-protein in radiation-exposed NSCLC cells. In addition, JNK phosphorylation was upregulated by delphinidin pre-treatment in radiation-exposed NSCLC cells. Collectively, these results show that delphinidin acts as a radiation-sensitizing agent through autophagy induction and JNK/MAPK pathway activation, thus enhancing apoptotic cell death in NSCLC cells.